2022
DOI: 10.1007/s10528-021-10175-3
|View full text |Cite
|
Sign up to set email alerts
|

Key Genes Associated with Tumor-Infiltrating Non-regulatory CD4- and CD8-Positive T Cells in Microenvironment of Hepatocellular Carcinoma

Abstract: The immune microenvironment in hepatocellular carcinoma (HCC), especially T-cell infiltration, plays a key role in the prognosis and drug sensitivity of HCC. Our study aimed to analyze genes related to non-regulatory CD4+ and CD8+ T cell in HCC. Data of HCC samples were downloaded from The Cancer Genome Atlas (TCGA) database. According to stromal and immune score retrieved by Estimation of Stromal and Immune cells in Malignant Tumor tissues using Expression data (ESTIMATE) algorithm, differentiated expressed g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 57 publications
0
1
0
Order By: Relevance
“…Therefore, targeted regulation of these two processes may be an important strategy for the treatment of virus-related HCC. The immune response that lymphocytes are widely suppressed is related to the development of HCC (41,42). Hence the infiltration of two T cell subtypes in the lesion site decrease, was observed.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, targeted regulation of these two processes may be an important strategy for the treatment of virus-related HCC. The immune response that lymphocytes are widely suppressed is related to the development of HCC (41,42). Hence the infiltration of two T cell subtypes in the lesion site decrease, was observed.…”
Section: Discussionmentioning
confidence: 99%
“…This binding inhibits the immune response initiated by the interaction of T cell CD28 with CD80/86. 203 In HCC tissues, exhaustion markers such as PD-1, CTLA-4, TIM-3 and LAG-3 are expressed at higher levels in CD8 + T cells compared with those in CHB liver tissues. 128 It has shown that serum CTLA-4 levels progressively increase from HBV carrier status through chronic hepatitis and cirrhosis to HCC, compared with healthy controls.…”
Section: Pd-1mentioning
confidence: 90%
“…This binding inhibits the immune response initiated by the interaction of T cell CD28 with CD80/86. 203 …”
Section: Anti‐tumour Immunity Of Cd8 + T Cells Bec...mentioning
confidence: 99%
See 1 more Smart Citation